1978
DOI: 10.1002/pol.1978.180161001
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐state and dynamic rheology of poly(1‐olefin) melts

Abstract: SynopsisThe steady-state and dynamic melt rheology for a series of poly( 1-olefins) has been investigated. The series includes poly(1-butene), poly(1-hexene), poly(1-heptene), poly(1-octene), poly(1-undecene), poly(1-tridecene), poly(1-hexadecene), and poly(1-octadecene). The flow behavior was investigated by use of a Weissenberg rheogoniometer. Measurements on poly(1-butene) were also made using an Instron capillary rheometer. The empirical relationship developed by Cox and Merz was obeyed for the entire seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…This is in accordance with Wang et al [50], who found a significant decrease of & 0 for longer poly-!-olefins in comparison to PE. However, it remains puzzling why the sample F26F [51] has almost the same weight comonomer content w c (having fewer but longer butacosene (C24) side chains) yet obeys the & 0 -M w -correlation of HDPE [38].…”
Section: Rheology 331 Zero Shear-rate Viscosity !supporting
confidence: 82%
“…This is in accordance with Wang et al [50], who found a significant decrease of & 0 for longer poly-!-olefins in comparison to PE. However, it remains puzzling why the sample F26F [51] has almost the same weight comonomer content w c (having fewer but longer butacosene (C24) side chains) yet obeys the & 0 -M w -correlation of HDPE [38].…”
Section: Rheology 331 Zero Shear-rate Viscosity !supporting
confidence: 82%
“…The data are summarized in Figure 3. We used the Cox–Merz rule23 [η*(ω) = η(γ˙)], which was found to be valid by earlier investigators24–31 for polyethylene and its copolymers, to obtain the steady shear viscosity. η 0 gives information about the zero shear viscosity.…”
Section: Methodsmentioning
confidence: 99%